Perceptions and Anticipation of Academic Literacy: ‘Finding Your Own Voice’ - Woods, Claire A.; Skrebels, Paul (Journal of Academic Writing, 2011)
Based on data gathered via survey questionnaire and follow up in-class discussion, the paper explores the ways undergraduate students think of themselves as writers and readers. Data drawn from a pilot survey in 2007 and a second in 2009 provides the impetus for discussion of issues of literacy and identity in a digital world. Of interest is 1) what first-year students anticipate they need to do and know, and 2) how final-year students reflect on what they have learnt in terms of academic literacies and related skills. A key issue is the way students bring a particular identity as readers and writers to university, and how this is transformed and re-inscribed through their studies. The importance of teaching for the development of rhetorical dexterity in a digital environment is highlighted because students’ digital literacy is a core element in their literacy identity. The paper also asks ‘how far should educators go in working into the space of digital literacies?’